Communication channel preferences by faculty members for faculty-student interaction - Nicole Yang Lai Fong,; Wan Idros Wan Sulaiman, (Universiti Kebangsaan Malaysian, 2011)
The most basic elements found within any educational settings are teachers and students (Dobransky and Frymier, 2004). Many scholars have argued the importance of positive teacher-student relationships (Frymier and House, 2000; Morganett, 1995; West, 1994), as well as the relationship between teacher-student relationships and learning (Chory and McCroskey, 1999; Dobransky and Frymier, 2004; Ellis, 2000). The impact of computer-mediated communication (CMC) in business and organizational communication has been the target of intense research, particularly since the 1990s (Keil and Johnson, 2002). The theoretical orientation builds on the assumption that face-to-face (FtF) communication possesses inherent characteristics that make it more appropriate than other channels, particularly channels that suppress too many of the FtF communication elements. However, Barnes (2003) proposed that the need to understand the impact of CMC on education is growing as technological advances offer more communication options. Therefore, this study focused on the faculty members’ communication channel preferences in faculty-student interaction. The study employed the Social Presence Theory and Media Richness Theory as the theoretical framework. A survey method was used with the questionnaires distributed to 50 faculty members at the University of Tunku Abdul Rahman. It was found that FtF communication, which leads to higher level of social presence and richness of information, was the most frequent used and preferred communication channel by the faculty members in faculty-student interaction.